Mental Emotional Changes in Children and Adolescents with Bronchial Asthma (Eurasian Medical Research Periodical, 2023)
The problem of the mechanisms of occurrence, course and treatment of psychosomatic disorders in children is becoming increasingly relevant for modern psychological science. The article presents an analysis of medical, social and psychological characteristics of children suffering from bronchial asthma, and from the risk group for its formation